Factors Causing Student Learning Difficulties in Following Online Learning and Teacher Guidance and Counseling Efforts to Overcome Them - Monalisa Marsedes; Yarmis Syukur (Current Issues in Counseling, 2021)
This research is motivated by the phenomenon of students experiencing a decline in grades in certain subjects, not understanding the use of learning applications and having difficulty concentrating on learning. This is due to changes in learning situations that were previously face-to-face turned into online learning. This study aims to describe the factors that cause student learning difficulties in participating in online learning and the efforts of counseling teachers to overcome them. This type of research is descriptive using quantitative methods. The study population consisted of 408 students of SMA Negeri 13 Padang who were registered in the odd semester of the 2020/2021 school year, with a sample of 202. The sample selection used a proportional random sampling technique. The data collection technique used a questionnaire with a Likert scale model. Data were analyzed using descriptive statistical techniques. The results showed that the factors causing student learning difficulties in participating in online learning were generally in the high enough category. And based on indicators (1) the low factor of technology use is in the high enough category with a percentage of 33.17%, (2) the limited factor of facilities and infrastructure is in the very low category with a percentage of 37.13%, (3) the limited internet network factor is in the very high category with a percentage of 28.71% (4) the limited cost factor of many students was in the quite high category, with a percentage of 38.12%. Furthermore, the counseling teacher's efforts in overcoming are in the high enough category and based on the indicators (1) the increase in learning motivation is in the loe category with a percentage of 58.91% (b) the development of attitudes and good learning habits is in the sufficient category high with a percentage of 32.67%.